Thermodynamic consistencies and anomalies among end-member lanthanoid garnets - Glasser, Leslie (Academic Press, 2014)
Lanthanoid (or lanthanide) garnets are ionic solids of technological importance in their use in electronic materials. They are also of interest in respect of their systematic relationships and as geochemical tracers. As a consequence, there is considerable published thermodynamic information for these garnets. Based principally on the computational results of Moretti and Ottonello (1998) [8], we here examine the thermodynamic information for consistencies and anomalies among the ferri-, alumino-, and gallo-garnets using relations between thermodynamic properties that we have established over recent years. The principal properties of interest are formula volume, heat capacity, entropy, and formation enthalpy (from which the Gibbs free energy may be obtained), and isothermal compressibility. We also establish additive single-ion values for trivalent lanthanide cations which may be applied in estimating properties for related materials. Since the results of the work of Moretti and Ottonello are based upon consistent computational analyses, we should expect generally smooth relations. These are, indeed, found for various of the properties (except for the europium garnets), with some uncertainty in the absolute entropies, and anomalies in the formation enthalpies of europium and ytterbium/lutetium garnets. The results of some more recent experimental work are included in our analyses. Values for the (unknown) promethium garnets are estimated by averaging the properties of the neighbouring neodymium and samarium garnets.